Prikaz nominalizacije v razpoložljivih korpusih slovenščine - Mikolič Južnič, Tamara (Slavistična revija, 2016)
The article is an attempt to provide an overview of the occurrence of nominalization in the Slovene language. A corpus-based methodology is used to compare original Slovene texts of different genres and translations from selected foreign languages (Italian, English, German, French). It appears that nominalization is highly dependent on register, but present in virtually all types of discourse.
Keywords: corpus analysis; grammar; grammatical metaphor; korpusna analiza; nominalizacija; nominalization; Slovene; Slovene language; slovenščina; slovnica; slovnična metafora